Structure du peuplement d’octopus vulgaris cuvier de la zone de l’Atlantique est-central (20°46’E - 19°36’N) - Maxim, Cornelia (Cercetări Marine - Recherches Marines, 2026)
The paper presents the results of the surveys carried out on Octopus vulgaris CUVIER, caught in the coastal area of the I. R. of Mauritania, during May - September 1982. There are presented the length and weight frequences, sex ratio, stages of maturity and length-weight relationship.